Monocyte and macrophage contributions to cardiac remodeling. (April 2016) - Hulsmans, Maarten; Sam, Flora; Nahrendorf, Matthias
Abstract: The mammalian heart contains a population of resident macrophages that expands in response to myocardial infarction and hemodynamic stress. This expansion occurs likely through both local macrophage proliferation and monocyte recruitment. Given the role of macrophages in tissue remodeling, their contribution to adaptive processes in the heart is conceivable but currently poorly understood. In this review, we discuss monocyte and macrophage heterogeneity associated with cardiac stress, the cell's potential contribution to the pathogenesis of cardiac fibrosis, and describe different tools to study and characterize these innate immune cells. Finally, we highlight their potential role as therapeutic targets. Highlights: Macrophages are an intrinsic part of the heart under physiological conditions. Cardiac macrophages expand in response to stress. Macrophage expansion through monocyte recruitment associates with cardiac remodeling Monocytes and macrophages may exert a wide range of pro- and anti-fibrotic actions.